Usefulness of Natural Phenolic Compounds in the Fight against Esophageal Cancer: A Systematic Review - Kamsu, Gabriel Tchuente; Ndebia, Eugene Jamot (Future pharmacology, 2024)
Esophageal cancer (EC) is a very common form of cancer in developing countries, and its exponential progression is a cause for concern. Available treatments face the phenomenon of multi-drug resistance, as well as multiple disabling side effects. The number of deaths is expected to double by 2030 if nothing is done. Due to their high representativeness in plants, phenolic compounds are a potential alternative for halting the spread of this disease, which bereaves many thousands of families every year. This study aims to identify phenolic compounds with activity against esophageal cancer, assess their toxicological profiles, and explore future perspectives. To achieve this, the literature search was meticulously carried out in the Google Scholar, Scopus, Web of Sciences, and Pub-Med/Medline databases, in accordance with the PRISMA 2020 guidelines. The results show that proanthocyanidin and curcumin represent promising therapeutic options, given their significant in vitro and in vivo activity, and their safety in human subjects in clinical trials. Moscatilin, Genistein, and pristimerin have anticancer activities (≤10 µM) very close to those of doxorubicin and 5-FU, although their safety has not yet been fully established. The compounds identified in vivo exhibit highly significant activities compared with the results obtained in vitro, and are sometimes more effective than the molecules conventionally used to treat EC. Generally, with the exceptions of plumbagin, lapachol, and β-lapachone, all other molecules are relatively non-toxic to normal human cells and represent a therapeutic avenue to be explored by pharmaceutical companies in the fight against esophageal cancer. However, more detailed toxicological studies of certain molecules remain a priority.